2012
DOI: 10.1002/ibd.21794
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between social support and autonomic function during a stress protocol in ulcerative colitis patients in remission

Abstract: Social support is related to parasympathetic activity in UC. Given previous evidence of an antiinflammatory role for the parasympathetic nervous system, this suggests that autonomic function could serve as a mediating link between social support and reduced inflammatory activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 46 publications
3
23
0
1
Order By: Relevance
“…Heinrichs et al, 2009; Meyer-Lindenberg et al, 2011; Porges, 2001). In addition, the present data are consistent with previous findings of an association between social support and elevated HRV (Maunder et al, 2012), as well as animal studies in which it has been found that oxytocin is associated with stress buffering effects on cardiac autonomic responses via increased vagal tone (Higa et al, 2002). Furthermore, these results confirm research on the OXTR polymorphism rs53576, which have shown that the A allele of rs53576 is associated with deficits in socioemotional domains (Bakermans-Kranenburg & van Ijzendoorn, 2008), reduced empathic accuracy (Rodrigues et al, 2009), lower positive affect (Lucht et al, 2009), heightened physiological stress reactivity (Rodrigues et al, 2009) as well as reduced social support seeking during times of distress when it is culturally normative (Kim et al, 2010), and reduced efficacy of social support (Chen et al, 2011).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Heinrichs et al, 2009; Meyer-Lindenberg et al, 2011; Porges, 2001). In addition, the present data are consistent with previous findings of an association between social support and elevated HRV (Maunder et al, 2012), as well as animal studies in which it has been found that oxytocin is associated with stress buffering effects on cardiac autonomic responses via increased vagal tone (Higa et al, 2002). Furthermore, these results confirm research on the OXTR polymorphism rs53576, which have shown that the A allele of rs53576 is associated with deficits in socioemotional domains (Bakermans-Kranenburg & van Ijzendoorn, 2008), reduced empathic accuracy (Rodrigues et al, 2009), lower positive affect (Lucht et al, 2009), heightened physiological stress reactivity (Rodrigues et al, 2009) as well as reduced social support seeking during times of distress when it is culturally normative (Kim et al, 2010), and reduced efficacy of social support (Chen et al, 2011).…”
Section: Discussionsupporting
confidence: 93%
“…Because the vagus nerve modulates the heart rate on a time scale of milliseconds, high frequency changes in heart rate, known as HRV, are a valid index of parasympathetic activation level (Thayer, Hansen, & Johnsen, 2008) and therefore for CNS stress regulation (Friedman & Thayer, 1998; Gianaros, Van der Veen, & Jennings, 2004; Thayer, Åhs, Fredrikson, Sollers, & Wager, 2012), at a high temporal resolution. A large body of evidence associating positive social interactions with increased HRV (Kok & Fredrickson, 2010; Maunder et al, 2012; Smith et al, 2011) further illustrates the usefulness of this index in the present research design. The basic data used for calculating HRV is the sequence of time intervals between consecutive heart beats, also known as inter-beat intervals (for more information on HRV, see Task Force of the European Society of Cardiology and the North American Society of Pacing and Electrophysiology, 1996).…”
Section: Introductionmentioning
confidence: 74%
“…The present study indicates that HF and TP were decreased after TNBS administration during experimental colitis, whereas the LF and LF/HF index were elevated. These data are also consistent with the clinical findings of autonomic dysfunction in IBD patients [14,15] and indicate that either the over-inhibition of the parasympathetic system and/or the over-excitation of the sympathetic system leads to disease progression. Additionally, we reveal that chronic VNS can regulate and rebalance the sympathetic-vagal balance, resulting in significant increases in HF and TP and decreases in LF and the LF/HF index within 6 days of TNBS administration.…”
Section: Discussionsupporting
confidence: 90%
“…Our previous work also demonstrated that biofeedback therapy can significantly improve vagal tone and can inhibit sympathetic activity [11,12]. The results of heart rate variability (HRV) analysis have shown that patients with IBD exhibited a higher level of sympathetic activity and a lower level of parasympathetic activity than healthy subjects, and a growing body of evidence suggests the existence of autonomic nervous system (ANS) dysfunctions in patients with IBD [13-15], which may also depend on the psychological adjustment of the patients [16]. Therefore, we speculate that Mind-Body interventions such as biofeedback might protect against the development of IBD by modulating sympathovagal balance and improving the psychological adjustment and adaptability.…”
Section: Introductionmentioning
confidence: 99%
“…En diferentes estudios relacionados con el apoyo social [32][33][34][35] y su repercusión en la evolución de la enfermedad queda demostrado cómo estamos ante un factor protector y minimizador de los brotes de EC. En nuestros resultados se han identificado diferentes ámbitos desde los que proviene dicho apoyo.…”
Section: Declaración De Conflicto De Interesesunclassified